ESCMID clinical guidelines on the evaluation and management of a reported antibiotic allergy - Joean, Oana; Sermet, Kevin; Ashkenazi-Hoffnung, Liat; Kiymaz, Yasemin Cakir; Blumenthal, Kimberly; Bonazzetti, Cecilia; Chiriac, Anca Mirela; Gomez-Zorrilla, Silvia; Karakike, Eleni; Khatamzas, Elham; Powell, Neil; Trubiano, Jason A.; et al. (Clinical microbiology and infection, 2026)
Scope - Antibiotic allergies remain one of the most frequently documented drug allergies in clinical records. It is well established that only a small proportion—estimated at 5% to 10%—represents true immune-mediated hypersensitivity. Mislabelling can contribute to the development of antimicrobial resistance via prescription of suboptimal antimicrobial therapy (i.e. unnecessary avoidance of first-line antibiotics), increased use of broad-spectrum agents, and complications such as drug toxicity. This guideline, developed by the European Society of Clinical Microbiology and Infectious Diseases, provides evidence-based recommendations for the clinical evaluation and management of patients with reported antibiotic allergies. It is aimed at nonallergist clinicians and seeks to harmonize practice across healthcare settings in Europe and beyond. - Methods - The guideline was developed by a multidisciplinary panel of 16 experts in infectious diseases, allergy, pharmacy, paediatrics and clinical microbiology, following a modified GRADE-ADOLOPMENT process. Systematic searches were conducted in PubMed and the Trip Database (2015-2023) to identify relevant guidelines, complemented by an additional systematic search for primary studies (2021-2024). The included guidelines were assessed using the AGREE Global Rating Scale. Four existing guidelines, from 2022 and 2023, met methodological quality criteria and were included. Key questions were identified and prioritized by the panel, and relevant data were extracted using piloted Evidence to Decision framework sheets. The panel developed recommendations by adopting, adapting or formulating new recommendations, through an iterative work-up and consensus process. All recommendations were finalized through panel discussion and formal voting, with consensus defined as agreement by ≥ 80% of members. - Recommendations - The guideline recommends a structured clinical assessment to evaluate a reported antibiotic allergy, taking into consideration the characteristics of the index reaction. Where the clinical history suggests a very low or low likelihood of true allergy, direct delabelling or performing a controlled drug challenge test is appropriate. By supporting allergy evaluation and prudent prescribing practices, the recommendations aim to improve individual patient outcomes and reinforce antimicrobial stewardship goals.